The Role of Sunstar-Davao in the Estrada administration's pursuit of the peace efforts with the CPP-NPA-NDF in Mindanao - Senga, Kristina P.
For so many years, efforts have been incessantly carried out by the Government of the Republic of the Philippines and the Community Party of the Philippines-New People's Army-National Democratic Front to find a lasting solution to the armed struggles in Mindanao. Yet, until the time of President Joseph Ejercito Estrada, bloodshed and ruins brought about by war in the Southern part of the country is still very much felt and seen. Various affected groups need to be supportive more than ever of the peace efforts coming from either side of the pole. And these include the press, especially the local press in Mindanao. Journalists from Mindanao should show their interest on peace-related events through the sound performance of their duties and responsibilities to the reading public. The research problem focused on is: How did that SunStar-Davao fare in its coverage of the Estrada administration's peace efforts with the CPP-NPA-NDF in Mindanao? For this thesis, the researcher made use of content analysis and semi-structured interviews. The analysis of the themes of the news articles, editorials, and columns of SunStar-Davao revealed that the most instances, the government is given more opportunity to express it side in stories related with the peace process, than is the CPP-NPA-NDF. On the other hand, the researcher discovered through the interviews conducted that there is a contrast in the way the national and local newspapers cover the peace process in Mindanao. The interviews also uncovered the fact that generally, stories related with the peace process are given little emphasis by SunStar-Davao. Other important matters disclosed in the interviews are the organizational and financial problems being faced by SunStar-Davao. These problems greatly affect the journalists' performance and leads to other problems like corruption as exposed by one of the interviewees. To back up these findings, the researcher relied upon different communication theories and read through related literatures that served as guide for the whole study.